The Impact of Domestic Economic Policy Uncertainty on Stock Returns in US States: An Empirical Study on the S&P500 Index - Yıldırım, Hakan (International Journal of Contemporary Economics and Administrative Sciences, 2025)
Uncertainties, which have significant effects on investment decisions, can have significant effects not only on investors’ decisions but also on investment instruments and markets. In this context, uncertainties that may arise in economic policies that closely concern stocks and investors, which have an important place among investment instruments, can complicate investment processes and cause pricing in securities markets to be subject to deviations. In this study, the effect of the local economic policy uncertainty (EPU) index on the price movements of the S&P500 stock market index in the US states, developed in Baker et al. (2022) and obtained from the digital archive of approximately 3500 local newspapers, is tested. The study, which includes 52 variables in total, utilizes the EPU index of 51 US states and the monthly data of the S&P500 (SPX) index, the leading stock market index of the US, for the period February 2006-December 2023. The findings of the Granger (1969) causality test indicate that there is no statistically significant causality from the EPU index data of states such as Arkansas, District of Columbia, Delaware, Minnesota, Nebraska, New Hampshire, Rhode Island and South Dokato to the price movements of the S&P500 stock market index, while there is a statistically significant causality from the EPU index of the other 43 states to the price movements of the S&P500 stock market index.